Analysis of horticulture farmers credit provision in Kemungsarilor Village, Panti District, Jember Regency - Abusiri, Mudahar; Santosa, Budi; Setiaji, Jatmiko (Journal of Agricultural Socio-Economics (JASE), 2024)
This study aims to analyze the factors influencing the success of credit provision to horticultural farmers in Kemuningsarilor Village, Panti Sub-district, Jember District, East Java. Given the capital-intensive nature of horticultural farming, access to credit is essential to support productivity. The research employed a census approach, using a saturated sampling technique that included all 50 farmers in the population. Data were analyzed using multiple linear regression to evaluate the influence of farmer experience, education, income, credit interest rates, and credit terms on the success of credit provision. The results indicate that farmer experience, income, interest rates, and credit terms significantly affect the success of credit provision, while education shows no significant impact. This is because, in rural agricultural settings, success in credit provision is more strongly influenced by practical farming experience, financial capability, and institutional criteria than by formal educational attainment. These results highlight the importance of strengthening farmers’ financial readiness and providing tailored credit schemes that consider their experiential knowledge rather than relying solely on formal qualifications. Future research is recommended to explore additional socio-economic and behavioral factors, such as financial literacy, access to farming advisory support, and risk attitudes, which may further explain variations in credit success among farmers.